Pregled sodobne programske opreme in spletnih aplikacij za matematike - 1. del - Bašić, Nino (Obzornik za matematiko in fiziko, 2015)
The mathematician's education in the information age demands not only the mastery of basic mathematical disciplines (e. g. algebra, analysis, etc.), but also familiarity with and skillful application of various software and web applications. In this article we present a review of contemporary mathematical software. Numerous links to free tools enable the reader to immediately try them out.
Keywords: computer science; računalništvo; programska oprema; brskalniki; iskalniki; večnamenska računska orodja; Sage; LaTeX; dinamična geometrija; učenje na spletu